2015
DOI: 10.1111/obr.12351
|View full text |Cite
|
Sign up to set email alerts
|

Chronobesity: role of the circadian system in the obesity epidemic

Abstract: Although obesity is considered to result from an imbalance between energy uptake and energy expenditure, the strategy of dietary changes and physical exercise has failed to tackle the global obesity epidemic. In search of alternative and more adequate treatment options, research has aimed at further unravelling the mechanisms underlying this excessive weight gain. While numerous studies are focusing on the neuroendocrine alterations that occur after bariatric Roux-en-Y gastric bypass surgery, an increasing amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 209 publications
(243 reference statements)
2
87
0
14
Order By: Relevance
“…Many disorders in glucose regulation, such as diabetes (Qian and Scheer, 2016) or obesity (Laermans and Depoortere, 2016), and their pharmacotherapies are also under robust circadian control. Recently, systems approaches have aimed at studying the dynamics of the circadian processes possibly impacting on energy metabolism.…”
Section: Systems Chronotherapeutics For Other Pathologiesmentioning
confidence: 99%
“…Many disorders in glucose regulation, such as diabetes (Qian and Scheer, 2016) or obesity (Laermans and Depoortere, 2016), and their pharmacotherapies are also under robust circadian control. Recently, systems approaches have aimed at studying the dynamics of the circadian processes possibly impacting on energy metabolism.…”
Section: Systems Chronotherapeutics For Other Pathologiesmentioning
confidence: 99%
“…Recent meta-analyses have associated shift work with an increased risk of obesity with workers having a greater predisposition to weight gain than their day-working counterparts (Amani & Gill, 2013;Antunes et al, 2010;Barbadora et al, 2013;Eberly & Feldman, 2010). A poor diet and physical inactivity (Atkinson et al, 2008), altered nutritional metabolism (Esquirol et al, 2009;Laermans & Depoortere, 2016), access to food (Stewart & Wahlqvist, 1985), desynchronisation of circadian rhythms (Antunes et al, 2010) and altered sleeping patterns (Mota et al, 2013) may all contribute to the observed increased risk of obesity. In addition to being associated with obesity, shift work has been identified as an independent risk factor for cardiovascular disease (Brown et al, 2009;TĂźchsen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…If the light-OPN3 adipocyte pathway exists in humans, there are potentially broad implications for human health. Our modern lifestyle subjects us to unnatural lighting spectra, exposure to light at night, shift work and jet-lag, all of which result in metabolic disruption (Fonken and Nelson, 2014;Fonken et al, 2013;Laermans and Depoortere, 2016;Opperhuizen et al, 2017). Based on the current findings, it is possible that insufficient stimulation of the light-OPN3 adipocyte pathway is part of an explanation for the prevalence of metabolic deregulation in the industrialized nations where unnatural lighting has become the norm.…”
Section: White Adipocytes Are a Crucial Site Of Opn3 Activitymentioning
confidence: 64%